The Place of Infants in the Evolving Australian Policy Context. Issue 4 (December 2014) - Fleet, Alma; Farrell, Lynn
IN AUSTRALIA, FEDERAL INITIATIVES have prioritised the education, care and wellbeing of young children through a government agenda delivering an Early Years Learning Framework (DEEWR, 2009) and a package of National Quality Standards (ACECQA, 2011). While research is available on appropriate practices for working with young children, little research is available, however, related to the impact on settings working with these documents. This paper shares research on the perceptions of the potential or actual impact of the evolving policy context as explored through interviews with 20 educators working with very young children. Issues are raised regarding staff development and qualifications in relation to educator understanding of the evolving policy context.